2016
DOI: 10.1111/psyp.12672
|View full text |Cite|
|
Sign up to set email alerts
|

Reward‐related neural dysfunction across depression and impulsivity: A dimensional approach

Abstract: Recent theoretical models underline reward sensitivity as a potential endophenotype for major depressive disorder. Neural and behavioral evidence reveals depression is associated with reduced reward sensitivity. However, reward dysfunction is not unique to depression, as it is also common across disorders of poor impulse control. We examined the interrelationships of depression (Depression, Anxiety, and Stress Scale [DASS-21]) and impulsivity (UPPS-P Impulsive Behavior Scale) with reward sensitivity among a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 90 publications
1
28
0
Order By: Relevance
“…Also, depression symptoms increased with the CD symptoms and callous-unemotional traits 37). Interestingly, the latest theoretical models predict that depression shares a common potential endophenotype, or reward dysfunction, with the impulsivity-based disorders including substance abuse, which is substantiated by accumulating physiological grounds 3841). Also, a large-scale twin study reported that the genetic covariation between depression and AUD could be explained by negative emotionality and behavioral control 42).…”
Section: Discussionmentioning
confidence: 99%
“…Also, depression symptoms increased with the CD symptoms and callous-unemotional traits 37). Interestingly, the latest theoretical models predict that depression shares a common potential endophenotype, or reward dysfunction, with the impulsivity-based disorders including substance abuse, which is substantiated by accumulating physiological grounds 3841). Also, a large-scale twin study reported that the genetic covariation between depression and AUD could be explained by negative emotionality and behavioral control 42).…”
Section: Discussionmentioning
confidence: 99%
“…Adopting a dimensional approach toward defining risk‐taking propensity and neural differentiation between gains and losses may help to clarify the transdiagnostic utility of these constructs and inform our understanding of psychopathology. Initial work examining the interrelationships of reward responding and externalizing traits has demonstrated that different biobehavioral profiles (e.g., low RewP amplitude and low impulsivity) can predict depressive symptoms (Ait Oumeziane & Foti, ). Further study of the interactions among neural and behavioral systems as they relate to symptoms may help to explain how clinically distinct psychopathologies arise from similar core features, such as reduced response to reward compared to loss.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical populations, a blunted RewP has been associated with depression (Foti & Hajcak, ; Liu, Wang, Shang, Shen, & Li, ; Nelson, Perlman, Klein, Kotov, & Hajcak, ; Weinberg, Liu, & Shankman, ) and vulnerability to depression (Bress et al, ; Foti, Kotov, Klein, & Hajcak, ; Kujawa, Proudfit, & Klein, ; Weinberg, Liu, Hajcak, & Shankman, ). Studies have also shown a blunted RewP in individuals high in broad externalizing traits (Bernat, Nelson, Steele, Gehring, & Patrick, ; although see Ait Oumeziane & Foti, ) as well as in substance abusing samples (Baker, Stockwell, Barnes, Haesevoets, & Holroyd, ; Baker, Stockwell, Barnes, & Holroyd, ) and problem gamblers (Hewig et al, ; Oberg, Christie, & Tata, ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…While preparing an unrelated follow‐up project using the original sample, the authors of Ait Oumeziane and Foti () found an error wherein approximately fifty percent of the study data was affected. We have corrected this error, and the corrected results are shared here.…”
Section: Correlations Between Predictors and Neural Measuresmentioning
confidence: 99%